2004
DOI: 10.1111/j.1523-1739.2004.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Weekend Road Traffic on the Use of Space by Raptors

Abstract: The traffic load near large cities may show dramatic cyclical changes induced by weekend tourism, and this could induce cyclical changes in the activity patterns of wildlife. We studied a 19-km-long section of a road that crossed a high-use raptor area near a large city in Spain. We observed 18 raptor species along this segment of the road, including some threatened species, such as the Spanish Imperial Eagle (Aquila adalberti). The number of cars increased dramatically on Saturdays and Sundays, so we assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 27 publications
4
96
1
2
Order By: Relevance
“…Similarly, non-natural mortalities attributed to illegal poisoning were the main mortality factors in other Bearded Vulture populations (Margalida et al 2008) and other large raptor populations (Whitfield et al 2004, Smart et al 2010, and collisions with power lines are known to threaten other vulture species in Africa (Smallie andVirani 2010, Boshoff et al 2011). Impacts related to human disturbance were also found to limit the distribution patterns of Bearded Vulture and other large raptor breeding ranges, densities, and foraging areas (Brown 1988, Herremans and Herremans-Tonnoeyr 2000, Donázar et al 2002, Bautista et al 2004, Gavashelishivili and McGrady 2006, Margalida et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, non-natural mortalities attributed to illegal poisoning were the main mortality factors in other Bearded Vulture populations (Margalida et al 2008) and other large raptor populations (Whitfield et al 2004, Smart et al 2010, and collisions with power lines are known to threaten other vulture species in Africa (Smallie andVirani 2010, Boshoff et al 2011). Impacts related to human disturbance were also found to limit the distribution patterns of Bearded Vulture and other large raptor breeding ranges, densities, and foraging areas (Brown 1988, Herremans and Herremans-Tonnoeyr 2000, Donázar et al 2002, Bautista et al 2004, Gavashelishivili and McGrady 2006, Margalida et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Higher predation rates along the freeway due, for example, to reduced concealment from potential predators and higher predator densities may also contribute to higher mortality rates along the freeway. Studies of predator densities along large roads have found inconsistent responses among species, with examples of positive, negative, and neutral population responses all seemingly evident (Meunier et al 2000, Bautista et al 2004, Fahrig and Rytwinski 2009. Whether predator populations are at higher densities along the Hume Freeway than populations at control sites is yet to be determined, as is qualification of whether this translates into higher predation rates of squirrel gliders along the freeway.…”
Section: Reduced Apparent Annual Survival Ratementioning
confidence: 99%
“…We overlaid distance maps to transportation infrastructure with distribution maps (10 × 10-km cells) (44) of six emblematic species of the Iberian fauna known to be negatively affected by roads at local scales: Strix aluco (Tawny owl), Otis tarda (Great bustard), Aquila adalberti (Spanish imperial eagle), Canis lupus (Gray wolf), Lynx pardinus (Iberian lynx), and Ursus arctos (Brown bear) (28,29,38,(45)(46)(47). For each species, we quantified the median distance to transport infrastructure in presence cells and classified resulting distances by bands of 500 m from the nearest infrastructure for graphical representation as a normalized histogram.…”
Section: Methodsmentioning
confidence: 99%